Clinicopathological factors associated with death from thin (≤ 1·00 mm) melanoma. (1st April 2020) - Claeson, M.; Baade, P.; Brown, S.; Soyer, H.P.; Smithers, B.M.; Green, A.C.; Whiteman, D.C.; Khosrotehrani, K.
Summary: Background: Thin cutaneous melanomas (≤ 1·00 mm) are increasing worldwide, causing around a quarter of all melanoma deaths in the U.S.A. and Australia. Identification of predictive factors for potentially fatal thin melanomas could allow better use of resources for follow‐up. Objectives: To identify the clinicopathological factors associated with fatal thin melanomas. Methods: This large, nested case–case study extracted data from the population‐based Queensland Cancer Registry, Australia. Our cohort consisted of Queensland residents aged 0–89 years who were diagnosed with a single, locally invasive thin melanoma (≤ 1·00 mm) between 1995 and 2014. Fatal cases (eligible patients who died from melanoma) were individually matched to three nonfatal cases (eligible patients who were not known to have died from melanoma) according to sex, age, year of diagnosis and follow‐up interval. Using conditional logistic regression, we calculated odds ratios (ORs) for melanoma‐specific death, adjusting for all collected clinicopathological variables. Results: In the cohort, 27 660 eligible patients were diagnosed with a single, thin melanoma. The final case–case series included 424 fatal cases and 1189 nonfatal cases. Fatal cases were sixfold as likely to arise on the scalp as on the back [OR 6·39, 95% confidence interval (CI) 2·57–15·92] and six times as likely to be of thickness 0·80–1·00 mm as of < 0·30 mm (OR 6·00, 95% CI 3·55–10·17). Conclusions: Scalp location is a strong prognostic factor of death from thin melanoma. Further, this study provides support that melanomas with a thickness of 0·80–1·00 mm are the more hazardous thin lesions. Patients with these tumour characteristics require specific attention during follow‐up. What's already known about this topic? Thin invasive melanomas (≤ 1·00 mm) contribute a substantial proportion of melanoma fatalities, owing to the high volume of disease. There is a need to find prognostic factors that will better identify fatal thin melanomas at the time of diagnosis. What does this study add? In this large population‐based study, fatal thin tumours were sixfold as likely to be located on the scalp as on the back. Thin melanomas of 0·80–1·00 mm thickness were six times as likely to be associated with death as tumours < 0·30 mm. Scalp location and increasing thickness are strong predictive factors of fatal thin melanomas, indicating that patients with these tumour characteristics require close follow‐up.